State-of-the-art research and application of SMAs technologies : "state-of-the-art research and application of SMAs technologies," Advances in science and technology, 59 : proceedings of the focused session A-10 "state-of-the-art research and application of SMAs technologies" of symposium A "smart materials and micro/nanosystems," held in Acireale, Sicily, Italy, June 8-13 2008 as part of CIMTEC 2008--3rd International conference "Smart materials, structures, and systems" - Vincenzini, P., 1939-; Besseghini, S. (Stefano) (Advances in science and technology (Faenza, Italy), 2009)
A select collection of 29 peer-reviewed papers together offering a great deal of timely information on, ""State-of-the-art Research and Application of SMAs Technologies"". The papers are conveniently arranged under the succinct headings: chapter 1: Materials; chapter 2: Phase transformation and microstructure; chapter 3: Engineering; chapter 4: Applications. This special volume has also been published online in the series, ""Advances in Science and Technology"" Vol. 59